Organic matter amendment regulates surface electrochemical properties of yellow soils: The major role of Alkyl C and O-Alkyl C - Xiaoshuai Song; Cheng Liang; Chenyang Liu; Lin Ning; Xiheng Lv; Wei Liu; Rena Yasin; Yunhang Luo; Jiangwen Li; Chenyang Xu; Wei Du; Wuquan Ding; et al. (Soil and Tillage Research, 2026)

Bamboo expansion into broadleaf forests restructures topsoil carbon, nitrogen, phosphorus and potassium pools: A trade-off between carbon sink enhancement and nutrient limitation - Qiudi Wu; Xin Wang; Bing Ma; Hongwei Zhou; Chenyang Huang; Liangjie Wang; Youjin Yan; Ziqiang Liu; Lina Mei; Haibo Hu; Lin Chen; Fengling Gan; et al. (CATENA, 2026)

Transitional strategy for food waste management in Hong Kong: Towards 2035 scenarios using prospective life cycle assessment - Chenyang Wang; Yahui Miao; Xiaohui Hu; Huaimin Wang; Shauhrat S. Chopra; Lu Sun; Liang Dong; Carol Sze Ki Lin (Resources, Conservation and Recycling, 2026)

Specific ion effects on the rheological properties of soils from the Loess Plateau of China - Xiaoshuai Song; Chenyang Xu; Yanan Zhang; Jiangwen Li; Wei Du; Xinmin Liu; Wuquan Ding; Fengbao Zhang; Lin Zhou; Stephan Peth; Feinan Hu (Soil and Tillage Research, 2026)

Machine learning based efficiency maximization of bio-Fenton SBR for enhanced antibiotic removal - Chenyang Lin; Tong Shen; Yuga Yoneyama; Yoshihiko Inagaki; Yutaka Sakakibara (Journal of Environmental Chemical Engineering, 2026)

Influence of gas reservoir volume on the secondary heat load required for cryogenic loop heat pipe startup - Chenyang Zhao; Lingji Hua; Nanxi Li; Bingyao Lin; Baoyu Yang; Zhenhua Jiang (International Journal of Refrigeration, 2026)

Flame impingement to facilitate the stability of NH3-CH4 laminar diffusion flames: High-speed imaging and schlieren visualization - Yidu Tong; Chenyang Fan; Zheng Fu; Ye Liu; Huiyong Du; Bin Xu; Guorong Lin; Shuo Jin; Shuainan Yang; Mingliang Wei (Fuel, 2026)

Beyond Borders: Tracking Water and Carbon Footprints of Global Transport Modes - Chenglong Wang; Xuewei Guo; Chenyang Shuai; Xi Chen; Wei Huang; Lin Gan; Jingran Sun; Bu Zhao (Water Resources Management, 2026)

Effect of aggregate size composition and matric potential on microstructural resistance and viscoelasticity of black soil in Northeast China - Lin ZHOU; Zekai LI; Chenyang XU; Jiangwen LI; Wei DU; Feinan HU (Pedosphere, 2026)

Degradation Pathways of Kraft Lignin by Novosphingobium sp. THN1: Insights into Refractory Dissolved Organic Matter Transformation in Lake Ecosystems - Chenyang Deng; Liwen Zhang; Chun Qing; Yuange Yu; Haorui Zhao; Genyi Wu; Yiqing Lin (Environmental Processes, 2026)

Mechanistic Links Between Suspended Sediment Dynamics and Metal Partitioning Under Tidal Forcing: A Case Study of Quanzhou Bay - Yanbin Fan; Yunhai Li; Yunpeng Lin; Shangshang Yang; Zhijie Chen; Xiang Cao; Chenyang Wang; Shanshan Zhang; Jinzeng Jiang; Mingyang Jiang; Kaichao Wan (Journal of Marine Science and Engineering, 2026)
The coupling of physical transport and phase-transfer processes represents a fundamental mechanism governing metal cycling in estuarine systems under tidal oscillations. Taking Quanzhou Bay as a model system, we conducted continuous observations and sample collection at the river channel (Q1), the turbidity maximum zone (Q2), and the outer bay channel (Q3). The metals (Al, Ti, Ba, Cu, Mn, and Zn) were measured by ICP-MS to systematically investigate the distribution, transport, and inter-media transfer across multiple water layers under varying estuarine processes. Our findings demonstrate that particulate metal concentrations in Quanzhou Bay exhibit strong synchrony with suspended sediment concentrations (SSC) over tidal cycles, displaying a distinct sediment-following pattern controlled by alternating end members. Particulate metal fluxes during flood and ebb-tides generally followed the hierarchy Q1 > Q2 >> Q3. Notably, stations Q1 and Q2 were dominated by flood-tide fluxes with net transport directed landward, whereas Q3 was characterized by ebb tide dominance with net flux directed seaward—revealing a spatial division of labor between “inner bay retention/reallocation” and “outer bay channel export”. In contrast, dissolved metals exhibited marked element-specific responses to tidal forcing: Al and Ti increased during flood tides at stations Q1 and Q2, while Ba and Cu showed opposite trends, and Mn and Zn displayed more conservative behavior. Concurrently, solid/liquid partition coefficient (logKd) values for Al, Ti and Ba, Cu exhibited inverse patterns over tidal cycles, suggesting divergent adsorption–desorption regulation under identical hydrodynamic conditions that drives differential phase-transfer dynamics. These disparities likely reflect intrinsic chemical properties and source variations among the elements. This study elucidates, at the tidal timescale, the coupled processes of “alternating end-member control—estuarine filter modulation—concurrent channelized export and inner bay retention” in Quanzhou Bay, providing critical process-level insights for metal flux quantification and bay pollution remediation initiatives in an ecological restoration project.

Linking functional groups of organic fertilizers to soil properties, crop productivity, and yield: Evidence from a field experiment - Xiaoshuai Song; Jiangwen Li; Lin Ning; Chenyang Xu; Wei Du; Xinmin Liu; Wuquan Ding; Feinan Hu (Soil and Tillage Research, 2026)

A review of carbon sequestration by CO2 mineralization using industrial byproduct gypsum: Feedstocks, pathways, and process intensification - Chenyang Wang; Xiao Lin; Guoqiang Chen; Wenzhan Wang; Yijun Cao; Chongqing Wang (Journal of Environmental Chemical Engineering, 2026)

Performance of PEI-modified fumed silica monoliths with honeycomb structure for direct air capture of CO2 - Chenyang Lin; Yijun Wang; Yihang Liu; Takeshi Hagio; Baowen Zhou; Xinling Li; Zhen Huang (Gas Science and Engineering, 2026)

Graphene-enhanced perfluorosilane coating with an ultralow sliding angle prevents lunar dust adhesion - Xin Wang; Zekai Huang; Sheng Chen; Yue Ouyang; Shengyu Wu; Lingjun Wu; Jinwei Zhao; Yihang Wang; Shengyuan Dai; Yani Lin; Yi Wang; Zhigui Liu; et al. (Chemical Engineering Journal, 2026)

Lithofacies Identification and Classification Based on Least Squares Support Vector Machine Optimized by Sparrow Search Algorithm - Chenyang Mu; Zhongjie Guo; Guangxu Wang; Xiaoxiao Zhang; Cheng Qian; Changsong Lin; Yang Chen; Yougong Wang; Wei Wu (Mathematical Geosciences, 2026)

Failure mechanism of the critical safety distance between tunnels and karst caves subjected to multi-hole blasting dynamic load - Yu Chen; Jialong Deng; Linchong Huang; Hang Lin; Yixian Wang; Chenyang Zhao (Tunnelling and Underground Space Technology, 2025)

Maximizing removal efficiency via magnetite dosage in bio-Fenton SBR - Chenyang Lin; Tong Shen; Yuga Yoneyama; Yoshihiko Inagaki; Yutaka Sakakibara (Journal of Water Process Engineering, 2025)

Orientation construction and comparison of mercury removal sites by physical and chemical adsorption on cotton stalk biochar - Guoliang Li; Shuxiao Wang; Qingru Wu; Tao Yue; Jiajia Gao; Yali Tong; Mingyu Zhang; Lin Zhang; Chenyang Zhang; Sizhe Xie (Fuel, 2025)

Multifunctional Cu-engineered NH2-MIL-125Ti@ZnIn2S4 heterojunction with dual-channel H2O2 activation for ultrafast water-mediated Cr(VI) photoreduction - Guangyuan Chen; Wei Han; Chenyang Lin; Yubao Li; Shijian Zhou; Yan Kong (Chemical Engineering Journal, 2025)

Adsorption and oxidation of NO and N2O on soot surfaces: Evolution of functional groups - Shuo Jin; Chenyang Fan; Zheng Fu; Haizhao Li; Ye Liu; Bin Xu; Huiyong Du; Guorong Lin; Mingliang Wei (Fuel, 2025)

The longitudinal loading mode evaluation of fault-crossing tunnel by a new load equivalence method based on a Pasternak model - Tianqiang Wang; Ping Geng; Chenyang Xiang; Guoguo Liu; Qi Wang; Lin Deng; Shiqiang Ma (Bulletin of Engineering Geology and the Environment, 2025)

Effects of Pisha sandstone additions on microstructural stability of sandy soil in Mu Us Sandy Land, China - Lin Zhou; Jiangwen Li; Chenyang Xu; Wei Du; Zhe Liu; Feinan Hu (Soil and Tillage Research, 2025)

Large Ensemble Simulations of Climate Models for Climate Change Research: A Review - Pengfei Lin; Lu Yang; Bowen Zhao; Hailong Liu; Pengfei Wang; Wenrong Bai; Jing Ma; Jilin Wei; Chenyang Jin; Yuewen Ding (Advances in Atmospheric Sciences, 2025)

Systematical identification of regulatory GPCRs by single-cell trajectory inference reveals the role of ADGRD1 and GPR39 in adipogenesis - Chuan Ye; Xuemei Wang; Jun Lin; Chenyang Wu; Yuhua Gao; Chenghao Guo; Yunxi Liao; Ziyan Rao; Shaodong Huang; Weixuan Chen; Ying Huang; Jinpeng Sun; et al. (Science China Life Sciences, 2025)

The mechanism of egg white protein to enhance the thermal gel properties of giant squid (Dosidicus gigas) surimi - Fuge Niu; Xiang Li; Chenyang Lin; Xinyu Hu; Bin Zhang; Weichun Pan (Food Chemistry, 2025)

Bioactivities, preparation, and bioavailability of food-derived proline-containing peptides - Chenyang Wang; Chibuike C. Udenigwe; Lin Zheng; Mouming Zhao (Trends in Food Science & Technology, 2025)

Formation mechanism of giant squid myofibrillar protein aggregates induced by egg white protein during heat treatment - Fuge Niu; Chenyang Lin; Huabin Liao; Bin Zhang; Jian Zhang; Weichun Pan (Food Hydrocolloids, 2025)

piggyBac-based transgenic Helicoverpa armigera expressing the T92C allele of the tetraspanin gene HaTSPAN1 confers dominant resistance to Bacillus thuringiensis toxin Cry1Ac - Lin Li; Xinru Pang; Chenyang Wang; Yihua Yang; Yidong Wu (Pesticide Biochemistry and Physiology, 2024)

Impacts of salinity stress induced by ballast water discharge on the ecosystem of shanghai port, China - Chenyang Duan; Lei Hu; Xiangbin Lin; Junzeng Xue; Jin Zou; Huixian Wu (Marine Environmental Research, 2024)

Enzymatic characterization and synergistic effects of protease combinations on DPP-IV inhibitory peptide release from bovine casein - Chenyang Wang; Lin Zheng; Chibuike C. Udenigwe; Lianzhu Lin; Mouming Zhao (Food Bioscience, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Synergistically Augmenting Cancer Immunotherapy by Physical Manipulation of Pyroptosis Induction - Chenyang Zhao; Tingting Zheng; Run Wang; Xiaona Lin; Zhengming Hu; Zhuofei Zhao; Zhifei Dai; Desheng Sun (Phenomics, 2024)
Pyroptosis is a newly recognized type of programmed cell death mediated by the gasdermin family and caspase. It is characterized by the formation of inflammasomes and the following inflammatory responses. Recent studies have elucidated the value of pyroptosis induction in cancer treatment. The inflammatory cytokines produced during pyroptosis can trigger immune responses to suppress malignancy. Physical approaches for cancer treatment, including radiotherapy, light-based techniques (photodynamic and photothermal therapy), ultrasound-based techniques (sonodynamic therapy and focused ultrasound), and electricity-based techniques (irreversible electroporation and radiofrequency ablation), are effective in clinical application. Recent studies have reported that pyroptosis is involved in the treatment process of physical approaches. Manipulating pyroptosis using physical approaches can be utilized in combating cancer, according to recent studies. Pyroptosis-triggered immunotherapy can be combined with the original anti-tumor methods to achieve a synergistic therapy and improve the therapeutic effect. Studies have also revealed that enhancing pyroptosis may increase the sensitivity of cancer cells to some physical approaches. Herein, we present a comprehensive review of the literature focusing on the associations between pyroptosis and various physical approaches for cancer and its underlying mechanisms. We also discussed the role of pyroptosis-triggered immunotherapy in the treatment process of physical manipulation.

Multi-metal Exposure and Liver Function in Elderly with Diabetes Mellitus: A Cross-Sectional Study in Eastern China - Jiujing Lin; Jia Li; Huichen Yao; Jinjie He; Xiangsheng Xue; Hengxia Zhao; Chenyang Hou; Xiaomei Li; Qingzhi Hou (Exposure and Health, 2024)

Corrigendum to “An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features” [Fuel 352 (2023) 128753] - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2024)

Beneficiation of silver and silver-bearing lead–zinc ores: A review - Hongliang Zhang; Heng Yu; Wei Sun; Shangyong Lin; Chenyang Zhang (Minerals Engineering, 2024)

ESG rating and financial risk of mining industry companies - Changluan Fu; Chenyang Yu; Mengting Guo; Lin Zhang (Resources Policy, 2024)

Impacts of salinity stress caused by ballast water discharge on freshwater ecosystems - Chenyang Duan; Min Yang; Qiong Wang; Junzeng Xue; Lin Yuan; Huixian Wu (Regional Studies in Marine Science, 2023)

Multifunctional graphene/Ag hydrogel with antimicrobial and catalytic properties for efficient solar-driven desalination and wastewater purification - Lin Lin; Wenrui Wang; Danyi Li; Siyi Xu; Ying Sun; Linfan Li; Kai Fan; Chenyang Xing; Lan Zhang; Jihao Li (Chemical Engineering Journal, 2023)

Soil C–N–P Stoichiometric Characteristics at the Aggregate Scales in Eucalyptus Plantations with Different Stand Types in Subtropical China - Yu Yan; Shengqiang Wang; Yuhong Cui; Chenyang Jiang; Jiazhen Deng; Mingye Lin; Shaoming Ye (Journal of Soil Science and Plant Nutrition, 2023)

Insights into the desilication mechanism of goethite by anionic reverse flotation from hydroxyl role - Hongliang Zhang; Shangyong Lin; Wei Sun; Daixiong Chen; Chenyang Zhang (Minerals Engineering, 2023)

Selective fabrication of hydrophilic BiOCl deposition layer on bismuthinite surface for efficient molybdenite/bismuthinite separation - Shangyong Lin; Hongliang Zhang; Xiangsong Meng; Ruolin Wang; Wei Sun; Haisheng Han; Chenyang Zhang (Minerals Engineering, 2023)

An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

Deep removal of fluoride from tungsten smelting wastewater by combined chemical coagulation-electrocoagulation treatment: From laboratory test to pilot test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Meirong Wu; Lei Yang; Huanjun Bao; Jianhua Kang; Haisheng Han; Chenyang Zhang; Wei Sun (Journal of Cleaner Production, 2023)

How do livelihood capital affect farmers' energy-saving behaviors: Evidence from China - Lin Li; Jianjun Jin; Chenyang Zhang; Xin Qiu; Dan Liu (Journal of Cleaner Production, 2023)

Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Huanjun Bao; Meirong Wu; Lei Yang; Gaogui Jing; Haisheng Han; Chenyang Zhang; Xiaoyun Jiang; Songlin Wang; Wei Ding; et al. (Journal of Environmental Management, 2023)

Exploring the effects of livelihood capital on clean cooking of rural households in the Tibetan region of China - Xin Qiu; Jianjun Jin; Chenyang Zhang; Dan Liu; Lin Li; Foyuan Kuang (Energy and Buildings, 2023)

Vegetable extracts: Effective inhibitors of heterocyclic aromatic amines and advanced glycation end products in roasted Mackerel - Simin Zhang; Ruichun Wang; Junbo Chu; Chenyang Sun; Songyi Lin (Food Chemistry, 2023)

Unfavorable geology recognition in front of shallow tunnel face using machine learning - Chenyang Zhao; Elham Mahmoudi; Maomao Luo; Mingjie Jiang; Peiyuan Lin (Computers and Geotechnics, 2023)

Removal of residual benzohydroxamic acid-lead complex from mineral processing wastewater by metal ion combined with gangue minerals - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Mengjie Tian; Chenyang Zhang; Ruohua Liu; Meirong Wu; Huanjun Bao; Wei Sun (Journal of Cleaner Production, 2023)

Phytochemical and chemotaxonomic investigations on the aerial parts of Cynanchum auriculatum Royle ex Wight - Yanling Xu; Chenyang Wu; Lu Wang; Shengbo Wu; Yueru Chen; Xiaoxue Ding; Lin Wang; Yi Yu; Weiming Du; Yuqing Zhang; Rachel Y.H. Yang; Jian Hong; et al. (Biochemical Systematics and Ecology, 2023)

Design of solar evaporator with well-aligned and multi-scale fluid channels based on convection tuning for stable and efficient brine desalination - Chenyang Dang; Xingtian Zhang; Lin Huang; Guiyin Xu; Li Gu; Xuebo Cao; Meifang Zhu (Desalination, 2023)

Effects of social capital on farmers’ choices of climate change adaptation behavior in Dazu District, China - Lin Li; Jianjun Jin; Rui He; Foyuan Kuang; Chenyang Zhang; Xin Qiu (Climate and Development, 2023)

Metal ions synergize with gangue minerals to remove residual sodium oleate from mineral processing wastewater - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Li Wang; Chenyang Zhang; Ruohua Liu; Huanjun Bao; Meirong Wu; Gaogui Jing; Wei Sun (Journal of Cleaner Production, 2023)

Dual-targeting celecoxib nanoparticles protect intestinal epithelium and regulate macrophage polarization for ulcerative colitis treatment - Ruijie Chen; Xinlu Lin; Qian Wang; Xingsi An; Xinyu Zhao; Yujie Lin; Tuyue Sun; Chenyang Yan; Aimin Cai; Weilan Cao; Youting Zhang; Qing Yao; et al. (Chemical Engineering Journal, 2023)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Spatial distribution of pollution characteristics and human health risk assessment of exposure to heavy elements in road dust from different functional areas of Zhengzhou, China - Huiliang Wang; Chenyang Shen; Yongfei Kang; Qiao Deng; Xiaoying Lin (Environmental Science and Pollution Research, 2020)

Mixed secondary chromatin structure revealed by modeling radiation-induced DNA fragment length distribution - Wenzong Ma; Chenyang Gu; Lin Ma; Caoqi Fan; Chao Zhang; Yujie Sun; Cheng Li; Gen Yang (Science China Life Sciences, 2020)

JcCBF2 gene from Jatropha curcas improves freezing tolerance of Arabidopsis thaliana during the early stage of stress - Linghui Wang; Jihai Gao; Xiaobo Qin; Xiaodong Shi; Lin Luo; Guozhen Zhang; Hongwu Yu; Chenyang Li; Minchao Hu; Qifan Liu; Ying Xu; Fang Chen (Molecular Biology Reports, 2015)